Politics of security : British and West German protest movements and the early Cold War, 1945-1970 - Nehring, Holger (2013)
Focuses on a number of peace movements in Britain and West Germany from the end of Second World War in 1945 to the early 1970s to understand how European societies experienced and reacted to the Cold War.